Plant Biotechnology; an Important Avenue for Medicine during Pandemics: Plant Biotechnology in times of Pandemics - Khan, Tariq; Amin, Iqra; Adil, Muhammad; Alam, Siyab; Khan, Sulaiman; Amin, Urooj; Ullah, Irfan; Aasim, Muhammad; Khan, Mubarak Ali (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
The coronavirus pandemic that is still ongoing has let the world learn many lessons. One of the lessons is to search for a viable source of medicine against such viruses. Vaccines for those ailing with symptoms of such viruses are most importantly needed from a viable source. Plant biotechnology offers a platform called Biopharming,wherein vaccines are produced in a safe, biocompatible manner. These vaccines also promise to have the advantage of being produced cost-effectively once the complete map of the process is laid down and is upscaled. Vaccines are undoubtedly developed at an unprecedented rate and are the most effective strategy to fight such pandemics. However, as understood from a fundamental standpoint, the vaccine is a part of a preemptive strategy. Along with synthetic chemical compounds, phytochemicals cannot be overlooked as candidates for drugs against Severe respiratory coronavirus 2 (SARS-CoV-2). Compounds, for instance, Glycyrrhizin from the roots of Glycyrrhiza glabra have been shown as a very promising phytochemical against the SARS-CoV, which caused an outbreak in 2002-2003. Other chemical compounds, reserpine, emodin, betulonic acid, and apigenin isolated from different plants, were also effective against SARS-CoV. The production of these and many other compounds through plant biotechnology techniques such as transgenesis and gene editing followed by in vitro cultures is a vital avenue to be considered. Transgenesis offers the advantage of boosted production of existing phytochemicals or triggered production of novel compounds through in vitro cultures which serve as a reactor for the development of important phytomedicine. This article emphasizes the role of Biopharming in the production of vaccines against SARS-CoV-2 and any such future outbreak causing Virus or bacteria. The report also highlights the role of transgenesis and gene editing to produce medicine against the Virus.